Campur Kode Dalam Web Series Kaget Nikah Karya Vemmy Sagita dan Implikasinya Dalam Pembelajaran Bahasa Indonesia Di SMA - Alicia Margareta; Albertus Purwaka; Patrisia Cuesdeyeni; Petrus Poerwadi; Nirena Ade Christy (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2024)
The general aim of this research is to describe the phenomenon of code-mixing in the dialogue of the main characters of the web series "Kaget Nikah" by Vemmy Sagita. The specific objectives of this research are: (1) to describe the forms of code-mixing in the web series "Kaget Nikah" by Vemmy Sagita. (2) to describe the factors causing code-mixing to occur in the web series "Kaget Nikah" by Vemmy Sagita. (3) to understand the implications of the forms of code-mixing and its contributing factors in drama education in eleventh-grade high school during the second semester. This research adopts a qualitative approach with a descriptive method. The data source for this research is the web series "Kaget Nikah" by Vemmy Sagita. The data in this research consist of code-mixing instances, including words, phrases, and clauses, as well as the factors causing code-mixing in the web series "Kaget Nikah" by Vemmy Sagita. Data analysis involves collecting, identifying, classifying, and describing the data. The results of this research indicate that (1) code-mixing occurs primarily at the word level, especially in the context of marriage; at the phrase level, particularly in the context of family; and at the clause level, especially in the context of sibling relationships in the dialogue of the main characters of the web series "Kaget Nikah" by Vemmy Sagita. (2) there are factors causing code-mixing in the dialogue of the main characters of the web series "Kaget Nikah" by Vemmy Sagita. (3) the findings of this research are utilized in drama education in eleventh-grade high school during the second semester, specifically focusing on competency 3.19.